Point-of-Care vs Laboratory Based Urine Protein-Creatinine Ratio as an Indicator of Proteinuria in Pregnancy [9N]. (May 2017) - Sinno, Omar; Rood, Kara M.; Jones, Megan; Thung, Stephen; Samuels, Philip; Buhimschi, Irina A.
Abstract : INTRODUCTION: Proteinuria is a hallmark finding in preeclampsia and a value of 300 mg or more in a 24 hour urine collection aids the diagnosis. A random urine protein-creatinine ratio (UPCR) of at least 0.3 mg/dL has emerged as a surrogate indicator of proteinuria. Point-of-care (POC) UPCR tests have been developed and may provide a convenient and timely extrapolation of proteinuria at the bedside. Although such testing has demonstrated excellent correlation with central laboratory methods in studies of non-pregnant patients, its validity and clinical utility have yet to be established in the pregnant population. Our objective was to evaluate POC UPCR as an indicator of proteinuria in pregnancy and compare it to the central laboratory method. METHODS: 108 urine samples from pregnant women presenting to triage for preeclampsia evaluation were collected prospectively from January to June 2015. For clinical purposes, a urine specimen was collected and sent to the laboratory for standard measurement of protein, creatinine and PC ratio using a Beckman Coulter Au5800, measuring turbidimetry by immunocomplexation with an anti-albumin antibody. A sample of the collected urine was tested via POC UPCR using Multistix Pro 11 reagent strips. Utilizing the manufacture interpretation guide, a "normal" strip ratio was defined as urine containing less than 300 mg protein/g creatinine. RESULTS: There was moderate agreement between POC UPCR and laboratory UPCR (k=0.512). After triage evaluation was complete, 31 women had a clinical diagnosis of preeclampsia. CONCLUSION: Results indicate that the POC UPCR is not reliable for the diagnosis of proteinuria when compared to the central laboratory UPCR.